การวิจัยและพัฒนารูปแบบการเสริมสร้างสมรรถนะทางวิชาการ โดยใช้กลยุทธ์การปรับโครงสร้างองค์กรของฟูลแลนสำหรับครูประถมศึกษา - ประไพ ธรมธัช (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purposes of this research were to develop an academic competency enhancement model adapting Fullan’s strategies for organizational restructuring for elementary school teachers and to study quality of the developed model. This model was developed through researching related documents and conducting fieldwork. The draft of the model was submitted to be reviewed by selected experts in the field of curriculum and instruction before being trial out in three selected elementary schools in Bangkok, one was categorized as an extra large school, another was large, and the last one was medium size school. Twenty four purposively selected elementary school teachers in the selected schools were involved in the study. Qualitative data were collected through participation observation with in-depth interviews, focus group interview, dialogue, and personal reflective journals techniques and analyzed through content analysis, and analytical induction while quantitative data analysis, mean, was used. Research findings were as the followings: 1. The ACE Model initiated to enhance the absence competency of the 24 teachers was composed of 3 essential elements: a) rationale and objectives, b) the 5 strategic plans emphasizing on 5 strategies as the followings 1) the caring goal sharing strategy 2) the self-knowledge creation strategy 3) the caring-trust-respect performance strategy 4) the create learning culture strategy, and 5) the collegial evaluation strategy, and c) the evaluation of academic competency occurring both during and after the utilization of the 5 strategies. 2. The quality of the ACE model could be explained through the competency level of the teachers . Both the teachers’ academic competency and the academic leadership competency were found to be elevated up to the good ( the third ) level. When scrutinizing individual competency category, it was found that: 2.1 The level of the academic competency in all instructional management category was elevated up to the good level. The instructional delivery competency was found to be the most accomplished dimension, followed by the instructional design competency dimension, and the instructional evaluation was found to be the least accomplished dimension. 2.2 The level of the academic leadership category was found to be elevated up to the good (the third) level in all dimensions, with the team working dimension was at the very good (level forth), and the communication dimension at the good (the third) level.